The Knowledge and Information of Vital Pulp Therapy by Libyan Internship Dentists and Dental Students: A Survey Study - Elkumati , Iman; Alawjali , Samia; abdullah, Arig; Alfetouri, Fatma; Betamar , Naeima (AlQalam Journal of Medical and Applied Sciences, 2025)
The dental pulp is a specialized connective tissue that maintains tooth vitality. Excessive wear or bacterial infiltration can cause irreversible pulp inflammation, often requiring pulpectomy or tooth extraction. Vital pulp therapy is considered a pulp-conserving treatment for permanent teeth. This study aims to evaluate the knowledge of Libyan dental interns and clinical-level students regarding vital pulp therapy (VPT) for permanent teeth, while also examining its correlation with their sociodemographic characteristics. A comprehensive survey consists of two parts: demographic and general information, followed by 22 questions assessing the understanding of vital pulp therapy’s indications, procedures, and materials. The questionnaire was mailed (as a soft copy) and distributed by hand (as hard copies) to internship dentists and clinical dental students from two Libyan academic centers in Benghazi. Descriptive statistics and the Chi-square test were used to analyze the responses to the questions. 71% of the 224 respondents were final year dental students, and 28.6% were internship dentists. (76.8%) Of the respondents were females; 23.2% were males. Only 36.2% of respondents knew that (VPT) may be successfully applied in teeth with signs and symptoms of irreversible pulpitis. 72.8% of respondents were familiar with the definition of indirect pulp capping. About 73.7% knew that any leakage to the capping materials would cause failure in VPT. 33.5% reported that Biodentine and TheraCal can be used as direct pulp capping agents. This study found that dental clinical-level students and interns possess a good understanding of the various types and procedural steps involved in Vital Pulp Therapy (VPT).